Ti-enhanced exfoliation of V2AlC into V2C MXene for lithium-ion battery anodes. Issue 14 (1st October 2017) - Zhou, Jian; Gao, Shaohua; Guo, Zhonglu; Sun, Zhimei
Abstract: Two-dimensional V2 C (MXene) derived from layered V2 AlC phase attracts increasing interest due to its various promising applications such as lithium-ion batteries. Yet it is a great challenge to obtain completely exfoliated V2 C MXene by etching Al from V2 AlC. Here, in this work, we highlight that alloying Ti can significantly enhance the exfoliation of (V1- x Ti x )2 C MXene from (V1- x Ti x )2 AlC based on our systematic studies of experiments and first-principles calculations. Furthermore, the exfoliated (V1- x Ti x )2 C MXene shows better multilayered morphology characterized by X-ray diffraction and scanning electron microscopy. Meanwhile, by analyzing the exfoliation process and electron localization functions, we have demonstrated that the micro-origin of Ti enhancement effect on the exfoliation of (V1- x Ti x )2 AlC is due to the significantly weakened interlayer bonding between the VC and Al layers in (V1- x Ti x )2 AlC induced by alloying Ti. Finally, we have shown that the performance of (V1- x Ti x )2 C as anode materials for Li-ion batteries is improved with the increase of Ti content. Our results provide a useful way to improve the synthesis of V-based MXenes and are beneficial to the applications as well.